Unpacking Academic Engagement: The Internal Drivers Shaping Undergraduate Students’ Learning Experiences - Qisthi Efridita (Journal of Psychological Insight, 2026)
Academic engagement is a critical factor influencing students’ learning outcomes and academic success in higher education. This study aims to explore the psychological factors that shape students’ academic engagement, focusing on motivation, self-efficacy, and positive emotions. Using a qualitative phenomenological approach, data were collected from ten undergraduate students through in-depth interviews, supported by observations and documentation, and analyzed using an interactive qualitative model. The findings show that students with strong intrinsic motivation demonstrate higher participation and initiative, those with high self-efficacy exhibit consistent persistence in completing academic tasks, and students experiencing positive emotions engage more actively in classroom interactions. This study contributes by integrating multiple psychological factors within a single analytical framework. The findings imply that educators should foster motivation, strengthen self-efficacy, and create supportive emotional environments to enhance students’ academic engagement.